Development of Ethnoscience-Based Science Learning Module Oriented Science Process Skills of Students - Siti Nur Ni’mah; Faiq Makhdum Noor (Yayasan Insan Mulia Bima, 2023)
The integration of local culture into science learning makes it easier for students to construct science concepts and still maintain local cultural knowledge. One of the science learning resources that can be used by students as well as a source of local culture learning is the ethnoscience-based science learning module. This study aims to (1) develop an ethnoscience-based module in the process of making batik and herbal medicine in science learning, (2) to find out the orientation of the science process skills of students in the use of an ethnoscience-based module. This research method uses a 4D Thiagarajan development model including the definition stage, the design stage, and the development stage. The dissemination stage was not carried out due to limited resources. The results of this study indicate that (1) The results of product development in the form of an ethnoscience module were developed through three stages, namely define, design, and develop; (2) the highest aspect of science process skills is observation with a score of 96% and the lowest aspect is interpreting observations and hypothesizing with a score of 47%. The results of the average score of science process skills from the seven aspects given were 62.5% in the good category.